An ultra-wideband bidirectional antenna with modified circular disc monopole excited elliptical ring - Chawanonphithak, Krittaya; Phongcharoenpanich, Chuwong; Kosulvit, Sompol; Krairiksh, Monai (My University, 2007)
The antenna design for ultra-wideband (UWB) signal radiation is one of the main challenges of the UWB system, especially when the antenna can satisfy the requirement of low-cost, compactness, linear polarization and bidirectional pattern. This paper proposes a UWB bidirectional antenna with introducing the ψ shape feeder to circular disc monopole (CDM) excited elliptical ring for modern base station in UWB system. The simulation results are presented UWB performance of this antenna by using Computer Simulation Technology (CST®). The return loss of better than 10 dB covers the frequency range from 3 to 25 GHz, directivity at the direction toward θ=0° and 180° from 2.8 dBi at 3 GHz to 4.6 dBi at 11 GHz. The proposed antenna can achieve bidirectional pattern over the bandwidth of 7.5 GHz. The bidirectional radiation pattern is desirable for many applications in long and narrow path service cell. ©2007 IEEE.
Keywords: Bidirectional antenna; Circular disc monopole; Ultra wideband